2018 Applied Aerodynamics Conference 2018
DOI: 10.2514/6.2018-3646
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Vortex Particle Code for the Modeling of Wake Interaction in Distributed Propulsion

Abstract: Recent developments in electric aircraft technology have enabled the use of distributed propulsion for the next generation of vertical lift vehicles. However, the ability to rapidly assess the performance of these design concepts, with sufficient fidelity, is a current weakness of this nascent industry. This paper explores the capacity of the viscous Vortex Particle Method (VPM) to model wake interactions found in distributed propulsion. The elements of the vortex particle method are summarized, and a new appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Reported error bars in the wind tunnel data are included in fig. 6b and are due to the dynamic nature of the propeller helical vorticies [26]. The two VLMs tend to follow the experimental trends except where the propeller swirl velocity induces wing upwash in the half-span regions between advance ratios 0.2 and 0.3.…”
Section: Propeller On Wing Validationsupporting
confidence: 52%
See 1 more Smart Citation
“…Reported error bars in the wind tunnel data are included in fig. 6b and are due to the dynamic nature of the propeller helical vorticies [26]. The two VLMs tend to follow the experimental trends except where the propeller swirl velocity induces wing upwash in the half-span regions between advance ratios 0.2 and 0.3.…”
Section: Propeller On Wing Validationsupporting
confidence: 52%
“…Propeller wakes generally reach their far-field values within approximately one rotor radius [26]. In this conceptual design study, we model the propeller as being removed one radius or more from the wing for the far-field values to be applied on the wing.…”
Section: A Propeller Aerodynamicsmentioning
confidence: 99%
“…The FMM approximates pairwise interactions of particles through spherical harmonic functions, 40,41 reducing the original computational complexity to a problem of order O(N ). The computation of the vortex stretching is performed through an efficient complex-step derivative approximation as explained in previous work, 21 implemented in a modified version of the open-source, parallelized FMM code ExaFMM. 42,43…”
Section: Iia3 Fast Multipole Methodsmentioning
confidence: 99%
“…In a previous study 21 we have shown that the VPM is able to fully characterize the evolution of the wake, from near field to far field and transition into turbulent breakdown. Furthermore, the VPM is a direct-numerical simulation approach, requiring an increased spatial resolution in the turbulent breakdown regime to ensure convergence.…”
Section: Iib Propeller Modelmentioning
confidence: 99%
See 1 more Smart Citation